Analisis Kebutuhan Belajar Siswa Sekolah Dasar dalam Pengembangan Bahan Ajar Tematik - Anisa Abdulrahman; Sri Meliyanti Djingo; Febriyanto Ali (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
The development of thematic teaching materials at the elementary school level requires a deep understanding of students’ learning needs to ensure that the presented material is relevant, contextual, and capable of improving learning outcomes. This study aims to analyze the learning needs of elementary school students as a basis for developing effective thematic teaching materials. Literature related to learning needs, teaching material design, integrated thematic approaches, and the characteristics of students’ cognitive development were analyzed comprehensively. The results of the study indicate that students’ learning needs include contextual material, concrete visualizations, collaborative activities, and varied learning media. Challenges include limitations of teachers in conducting needs analysis, suboptimal utilization of technology, and the suitability of material to the local context. This article provides strategic recommendations for designing student-needs-based thematic teaching materials that are adaptive, engaging, and competency-oriented.